If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = 4(y + -1) Reorder the terms: 36 = 4(-1 + y) 36 = (-1 * 4 + y * 4) 36 = (-4 + 4y) Solving 36 = -4 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 36 + -4y = -4 + 4y + -4y Combine like terms: 4y + -4y = 0 36 + -4y = -4 + 0 36 + -4y = -4 Add '-36' to each side of the equation. 36 + -36 + -4y = -4 + -36 Combine like terms: 36 + -36 = 0 0 + -4y = -4 + -36 -4y = -4 + -36 Combine like terms: -4 + -36 = -40 -4y = -40 Divide each side by '-4'. y = 10 Simplifying y = 10
| 5(x-100)=2(x-100) | | (y-8)-(y+6)= | | 4(5b-7)=10b+2 | | 5x+7y=-8 | | x+x+6=46 | | 13x+3(x+11)=8x-7 | | 6a+-92=2a | | g-2/5g=3 | | 1/3=k-4 | | 2(3x-6)=x+4+5x | | 7x-12=y | | 6*n-92=2 | | 4x^2-17x+10=-4x+1 | | 9n=15/7-2 | | s^2(s^2+1)=0 | | 20+4n= | | -17x=-20 | | 25+5n= | | 2x+5x=10+4 | | -40=10x+20 | | 6x^2+11x-22=0 | | x+2+x=3x-6-x | | -138=15x-x | | 2(x-11)=5x-19 | | 5.99x+3.99(x+2)+8.25(1)=41.18 | | 192x^2-1984x+5120=0 | | log(3x)+4log(5y)-3log(4z)= | | -5(2x+4)=30 | | 9(7x+5)=360 | | 52+4y-21=-15y-11-4y | | 2*3=5*3+6 | | x+23+4x=-12-4x-19 |